COVID-19 outbreak and rural household food security in the western Democratic Republic of the Congo - Manyong, Victor; Bokanga, M.; Dieu-Merci, A.N.; Bamba, Z.; Adeoti, R.; Mwepu, G.; Cole, Steven M.; Dontsop Nguezet, Paul M. (Elsevier, 2022)
Although global assessments of the initial impacts of the coronavirus disease (COVID-19) have focused on income, jobs, and health conditions, this study constitutes one of the first studies that assessed the impact of COVID-19 on food security in DRC and established the short-term implications of the COVID-19 outbreak on rural households’ food security in DRC. In addition, the study recommendations contributed to shaping government interventions toward the pandemic in the Country. The study used data from four western provinces of the country on 1339 households. Our results show that 80 % of households experienced an increase in food prices, 61 % a noticeable decrease in the availability of food, and 54 % a decrease in their dietary diversity. Due to changes in food availability, dietary diversity, and food accessibility imposed by the COVID-19 outbreak, >70 % of households experienced either a decrease in the consumption of meat, milk, fish, and cereals or an increase in their consumption of traditional vegetables. In addition, COVID-19 significantly affected food security dimensions in larger households, households with a greater number of members aged 35 years and above, households headed by women, households where members participate in associations or cooperatives, households that depend on crop sales as the major source of income, and in poorer households. These findings highlight the significant implications of the COVID-19 outbreak on household food security in western DRC and underscore the need for emergency interventions to strengthen the resilience of rural people and accelerate their recovery and other long-term measures toward sustainable and inclusive development.